Disparitas dan Konvergensi Pendapatan Perkapita Propinsi di Kawasan Timur Indonesia - Bima Prasetya Kumara; Toto Gunarto; Arivin Ratih (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study aims to identify per capita GRDP disparities in 13 provinces in Eastern Indonesia. The data used in this study is secondary data obtained from the website of the Badan Pusat Statistik (BPS). The analytical method used in this study is the Williamson index, panel data and convergence analysis. The results show that regional disparities using the Williams Index tend to decrease towards equity. Convergence analysis shows that there has been absolute beta convergence at a rate of 9.24 percent per year, conditional beta convergence analysis shows that there is no conditional beta convergence. Sigma convergence analysis shows a decrease in the dispersion of per capita income, which means that there has been a sigma convergence between provinces in Eastern Indonesia.